Business models for media firms : does competition matter for how they raise revenue? - Hans Jarle Kind; Tore Nilssen; Lars Sørgard (Center for Economic Studies and ifo Institute (CESifo), 2009)
The purpose of this article is to analyze how competitive forces may influence the way media firms like TV channels raise revenue. A media firm can either be financed by advertising revenue, by direct payment from the viewers (or the readers, if we consider newspapers), or by both. We show that the scope for raising revenues from consumer payment is constrained by other media firms offering close substitutes. This implies that the less differentiated the media firms' content, the larger is the fraction of their revenue coming from advertising. A media firm's scope for raising revenues from ads, on the other hand, is constrained by how many competitors it faces. We should thus expect that direct payment from the media consumers becomes more important the larger the number of competing media products.
Keywords: D21; 330; Medienwirtschaft; Geschäftsmodell; Einnahmen; Werbung; Rundfunkfinanzierung; Verbraucher; Wettbewerb; Komplementärgut; Produktdifferenzierung; Theorie